Grafik Tasarımda Akademik Araştırmalar 2 - Uslu, Yaşar; Yücelen, Bora Bekir; Diksoy, İlhami; İnanlı, Aslı; Demirkale Kukuoğlu, Oya Cansu; Güney Türkeç, Aysel; Yıldız, Münire; Dedeoğlu, Şerafettin (2024)
-